2019
DOI: 10.20892/j.issn.2095-3941.2018.0291
|View full text |Cite
|
Sign up to set email alerts
|

BRAFV600E vs. TIRADS in predicting papillary thyroid cancers in Bethesda system I, III, and V nodules

Abstract: Objective Bethesda System for Reporting Thyroid Cytopathology (BSRTC) categories I, III, and V account for a significant proportion of fine needle aspiration cytology (FNAC) diagnoses. This study aimed to compare the diagnostic efficacy of BRAF V600E mutation and the Thyroid Imaging Reporting and Data System (TIRADS) classification in differentiating papillary thyroid cancers (PTCs) from benign lesions among BSRTC I, III, and V nodules. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…For these reasons, several models have been proposed for the direct integration of molecular and sonographic data [100][101][102]. These models have yet to be validated in multicenter and prospective studies.…”
Section: Molecular Diagnosticsmentioning
confidence: 99%
“…For these reasons, several models have been proposed for the direct integration of molecular and sonographic data [100][101][102]. These models have yet to be validated in multicenter and prospective studies.…”
Section: Molecular Diagnosticsmentioning
confidence: 99%
“…The FNAC has been extensively employed to diagnose thyroid carcinoma and has proven to be reliable in preoperative diagnosis. However, FNAC fails to give definitive diagnosis when the results of the Bethesda System for Reporting Thyroid Cytopathology (BSRTC) are indeterminate for categories, such as in the case of atypia of undetermined significance/follicular lesion of undetermined significance (AUS/FLUS) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown the rates of malignancy in TBSRTC category I, III, and V nodules were 15.3%, 39.3%, and 96.8%, respectively, and BRAF V600E exhibited similar diagnostic performance to that of TIRADS in BSRTC III/V nodules, the combination of the two diagnostic approaches significantly enhanced the sensitivity, especially among high TBSRTC higher TIADRS score and a TBSRTC score. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%